A Quality Improvement Project to Reduce the 'No Show' rate in a Paediatric Neurology Clinic. Issue 1 (30th August 2016) - Mohamed, Khalid; Mustafa, Amira; Tahtamouni, Sona; Taha, Eshraga; Hassan, Reham
Abstract : This quality improvement project aimed to reduce the 'no show' rate in a paediatric neurology clinic in Qatar. No show, in outpatient clinics, is defined as patients who fail to attend their scheduled clinic appointments. It is one of the targets for improving quality of care. It leads to longer waiting times for patients to be seen in outpatient clinics, and the result is patients missing their important appointments. It also results in a waste of the clinic resources, and physician and other healthcare practitioners' time. This study was undertaken as part of the CCITP (clinical care improvement training programme). A project team was assembled with coaching support. The department chairman and the appointment system personnel were involved. Baseline and ongoing measures were collected and charted. The baseline no-show rate was identified as 49%. Following three intervention PDSAs, mainly addressing communication and appointment flexibility, the post intervention no-show rate dropped to 18% and was sustained below the target of 25% for two years. Better communication and appointment flexibility can significantly reduce the no-show rate in outpatient clinics.